Risk Factors, Patterns, and Long-Term Survival of Recurrence After Radiofrequency Ablation With or Without Transarterial Chemoembolization for Hepatocellular Carcinoma - Huang, Jingjun; Huang, Wensou; Guo, Yongjian; Cai, Mingyue; Zhou, Jingwen; Lin, Liteng; Zhu, Kangshun (Frontiers in Oncology, 2021)
Objectives: To classify hepatocellular carcinoma (HCC) recurrence patterns after radiofrequency ablation (RFA) or transarterial chemoembolization (TACE) combined with RFA (TACE-RFA) and analyze their risk factors and impacts on survival. Methods: We retrospectively evaluated the medical records of HCC patients who underwent RFA or TACE-RFA from January 2006 to December 2016. HCC recurrences were classified into four patterns: local tumor progression (LTP), intra-segmental recurrence, extra-segmental recurrence, and aggressive recurrence. Risk factors, overall survival (OS), and post-recurrence survival of each pattern were evaluated. Results: A total of 249 patients with a single, hepatitis-B virus (HBV)-related HCC ≤ 5.0 cm who underwent RFA (HCC ≤ 3.0 cm) or TACE-RFA (HCC of 3.1-5.0 cm) were included. During follow-up (median, 53 months), 163 patients experienced HCC recurrence: 40, 43, 62 and 18 patients developed LTP, intra-segmental recurrence, extra-segmental recurrence, and aggressive recurrence, respectively; the median post-recurrence survival was 49, 37, 25 and 15 months, respectively (P < .001); the median OS was 65, 56, 58 and 28 months, respectively (P < .001). Independent risk factors for each pattern were as follows: tumor sized 2.1-3.0 cm undergoing RFA alone and insufficient ablative margin for LTP, periportal tumor and non-smooth tumor margin for intra-segmental recurrence, HBV-DNA ≥ 2000 IU/mL for extra-segmental recurrence, and periportal tumor and α-fetoprotein ≥ 100 ng/mL for aggressive recurrence. Recurrence pattern (P < .001) and Child-Pugh class B (P = .025) were independent predictors for OS. Conclusions: Based on our classification, each recurrence pattern had different recurrence risk factors, OS, and post-recurrence survival.